Contract, Renegotiation, and Holdup: When Should Messages be Sent? - Daniel Göller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
I consider a setting of complete but unverifiable information in which two agents enter a contractual relationship to induce mutually beneficial investments. As my main result, I establish that the famous irrelevance of contracting paradigm, that arises due to the detrimental effect of renegotiation, is resolved if there is a fixed point in time when actions have to be chosen and one accounts for the fact that renegotiation takes time. What drives my optimality result is that, by stipulating when the mechanism is to be played, the agents ensure that renegotiation is possible ex ante but not ex post.
Keywords: D86; D82; K12; 330